Identification of Two GDSL-Type Esterase/Lipase Genes Related to Tissue-Specific Lipolysis in Dendrobium catenatum by Multi-Omics Analysis - Xinqiao Zhan; Yichun Qian; Bizeng Mao (Life, 2022)
Dendrobium catenatum is an important herb and widely cultivated in China. GDSL-Type Esterase/Lipase proteins (GELPs) are widely distributed in plants and play crucial roles in stress responses, plant growth, and development. However, no identification or functional analysis of GELPs was reported in D. catenatum. This study identifies 52 GELPs in D. catenatum genome, which is classified into four groups by phylogenetic analysis. Four conservative blocks (Ser-Gly-Asn-His) are found in most GELP domains. Transcriptome analysis reveals the expression profiles of GELPs in different organs and flowering phases. Co-expression analysis of the transcriptome and lipidome identifies a GELP gene, Dca016600, that positively correlates with 23 lipids. The purified Dca016600 protein shows the optimum pH is active from 8.0 to 8.5, and the optimum temperature is active from 30 °C to 40 °C. The kinetic study provides Vmax (233.43 μmol·min−1·mg−1) and Km (1.49 mM) for substrate p-nitrophenyl palmitate (p-NPP). Integrated analysis of the transcriptome and proteome identifies a GELP gene, Dca005399, which is specially induced by freezing. Interestingly, Dca005399 shows high expression in symbiotic germination seeds and sepals. This study provides new insights into the function of D. catenatum GELPs in plant development and stress tolerance.